Ethnographic study of democratic character values in Tradition Sko kenduri in Clean Water Village - Rusman, Hedi (International Journal of Education, Information Technology, and Others, 2024)
This study aims to explore democratic values embedded in the kenduri sko tradition in Air Bersih Village. A qualitative ethnographic approach was employed, utilizing participatory observation, in-depth interviews, and documentation for data collection. Data analysis involved organization, categorization, and interpretation to gain a comprehensive understanding of the tradition. The findings reveal that the kenduri sko tradition embodies democratic values such as deliberation, mutual cooperation, solidarity, transparency, equality, and inclusivity. These values are reflected in every stage of the tradition. The findings highlight that the kenduri sko tradition plays a crucial role in maintaining social harmony and strengthening democratic character within the community of Air Bersih Village